Properties and durability of metakaolin blended cements: mortar and concrete - Abbas, Rafik; Abo-El-Enein, Salah A.; Ezzat, El-Sayed (Materiales de Construcción, 2010)
This article explores the effect of metakaolin, a pozzolan, on concrete performance. Compressive and splitting tensile strength were found for specimens cured for up to 360 and 90 days, respectively. Changes were recorded in the compressive strength of specimens exposed to salt (chloride and sulfatechloride solutions), and chloride penetration and binding capacity were measured. The findings were compared to the results for concrete prepared with ordinary Portland (OPC) and moderate heat of hydration (Type II) cement. MK was found to have a very positive effect on 28-day concrete strength, due to microstructure improvement of the hydrated cement. Replacing cement with metakaolin effectively raised concrete resistance to chloride attack. Concrete containing metakaolin proved to be substantially more durable in sulfate-chloride environment.